The Effect of Government Policy Management on the Quality of Health Services - Wulan Rahmadhani; Umi Laelatul Qomar; Sangay Dorji (Disease Prevention and Public Health Journal, 2023)
Background: Quality of health services is a tool to measure the patient’s satisfaction with medical services in accordance with standard operating procedures and medical service standards. It is based on the potential of available resources, facilities, and infrastructure of Pusat Kesehatan Masyarakat (Puskesmas) or hospitals that are efficient, effective, safe, and in accordance with norms, ethics, law, as well as the socio-cultural environment while respecting and adapting to the capabilities and limitations of the government and society. Good quality of services in a health service affects the health service. This research aims to analyze, synthesize, summarize, and compare the results of studies about the influence of government policy management on the quality of health services in Puskesmas. Method: This literature review was conducted by searching the literature in Google Scholar, Prayer, and Garuda with the keywords of Government Policy, Health Service Management, and Quality of Health Services. This study reviewed 6 articles as reference sources. Results: This study showed the influence of government policy management on the quality of health services at Puskesmas. Conclusion: Policy management in a health service greatly influences the quality of health services and good service quality results in high patient satisfaction.